Study on the Influence Factors of Sustainable Energy Use Behavior - Tao, Yanhui; Khatibi, Ali; Tham, Jacqueline (International Journal of Natural Resources and Environmental Studies, 2025)
China is both the world's largest clean energy market and the world's largest polluter. However, nearly a third of the world's CO2 emissions also come from China. The Chinese government recognizes the importance of changing household lifestyles and energy consumption patterns to achieving the "two-carbon goal". Therefore, vigorously promote residential photovoltaic power generation (PV) and the transition from traditional fossil fuels to renewable energy sources (such as solar power generation). This paper studies the influencing factors on residents' willingness to conduct sustainable energy use.